(NqK sM)QÆ[ARIK Æ vARTUNXKA SMÆ[INOK WIZWOLQLI (B:s)E (NSWQTO DLQ D)QÆTEJ DO[K(B. (NWÆKU (B/s)E - (NrUBALXSXKA(B, (Nn(B.,s (2015)
(NsCENAR)QÆJ SWQTA DO dNQ GUMORU(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NdO[K)QÆLXNÆ NAW^ALXNÆ ZAKLADIs)E -- (NSCENAR)QÆÇs)E -- (NuKRA)QÇNAs)E; (NDO[K)QÆLXNÆ NAW^ALXNÆ ZAKLADIs)E; (NSCENAR)QÆÇs)E; (NdENX GUMORUs; (NSWQTO SM)QÆHUs)E; (NSWQTAs